(untitled) (Market-Tržište, 2025)
Purpose – This paper investigates how collaborative marketing strategies shape the tea tourism industry, promote sustainable development, and improve destination competitiveness. It addresses gaps in the literature by offering detailed insights into the role of collaborative marketing as part of industry development, sustainable practices, and destination appeal. Methodology – A systematic literature review of 52 peer-reviewed articles was conducted, including 42 written on tea tourism between 2006 and 2024 and 10 on market orientation theory dating from 1990–2022. Key themes and findings were identified and analyzed to understand the impact of collaborative marketing strategies. Findings and implications – The research highlights the pivotal role of collaborative efforts within the Destination Marketing System (DMS) framework and market-oriented approaches in tea tourism. It identifies a gap in the application of market-driving or collaborative market-driving strategies and suggests future research directions. Stakeholders can leverage insights to craft effective marketing strategies, integrate sustainable practices, and foster collaboration, thereby enhancing destination attractiveness and competitiveness. Limitations – The study is limited by its reliance on the existing literature and potential biases in article selection. Its scope is confined to peer-reviewed journals within the specified timeframe, which may affect the generalizability of the findings. Originality – This study contributes by synthesizing extant research on tea tourism marketing strategies within a comprehensive framework encompassing the DMS and market orientation theory, offering valuable guidance for academics, practitioners, and policymakers.